2023
DOI: 10.1155/2023/7698706
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-Induced miR-493-3p Inhibits Growth and Invasion of Gastric Cancer through Suppression of DKK1-Mediated Wnt/β-Catenin Signaling Activation

Abstract: Purpose. Gastric cancer (GC) is one of the most common malignant tumors and also one of the most deadly tumors. In recent years, studies have shown that propofol can inhibit the proliferation and metastasis of many tumor cells. In the present study, we aimed to investigate the underlying mechanism of propofol inhibition of the growth and invasion of GC cells. Methods. Human gastric cancer cell line SGC-7901 and human normal gastric epithelial cell GES-1 were cultured in high-glucose Dulbecco’s Modified Eagle’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Similarly, DKK1 has been shown to correlate with poorer sur- vival rates in GC patients, through mechanisms that involve the creation of an immunosuppressive tumor microenvironment [29]. Literature also suggests that DKK1 is targeted by anesthesia-induced miR-493-3p, which inhibits GC cell growth by repressing Wnt/β-catenin signaling and is implicated in GC cell invasion, proliferation, and drug resis-tance [30]. Given these precedents, FABP6 was selected as the focal prognostic marker for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, DKK1 has been shown to correlate with poorer sur- vival rates in GC patients, through mechanisms that involve the creation of an immunosuppressive tumor microenvironment [29]. Literature also suggests that DKK1 is targeted by anesthesia-induced miR-493-3p, which inhibits GC cell growth by repressing Wnt/β-catenin signaling and is implicated in GC cell invasion, proliferation, and drug resis-tance [30]. Given these precedents, FABP6 was selected as the focal prognostic marker for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that miR-493-3p plays a tumor suppressor role in ovarian cancer, non-small cell lung cancer, laryngeal squamous cell carcinoma, and glioma [ 24–27 ]. Kaishuai Zhan et al found that miR-493-3p can be induced by propofol and inhibit the growth and invasion of gastric cancer by inhibiting the activation of Wnt/β-Catenin signal mediated by DKK1 [ 28 ]. We found that circRNA_102191 sponge adsorbed miR-493-3p through qRT-PCR and dual luciferase experiments, and miR-493-3p could reverse the effect of circRNA_102191 on the biological behavior of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Various medications, including morphine, propofol, and sufentanil, have been used in clinical practice as part of PPC to prevent I/R injury. Previous studies have shown that morphine can activate Wnt/β-catenin signaling 491 493 ; propofol has a therapeutic effect against esophageal cancer, 494 gastric cancer, 495 hepatocellular carcinoma, 496 and colon cancer 497 by blocking Wnt/β-catenin signaling; Sufentanil inhibits the proliferation of lung cancer cells by suppressing Wnt/β-catenin signaling. 498 During PPC, Wnt/β-catenin signaling may be one of the molecular pathways involved in protecting organs from further damage.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%